2006
DOI: 10.1021/ja065444v
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Surface Functionalization of Periodic Mesoporous Silica:  Kinetic Control by Trisilazane Reagents

Abstract: The surface reactions of mesoporous silica MCM-41 with a series of new trisilylamines (trisilazanes) (SiHMe2)2NSiMe2R and (SiMe2Vin)2NSiMe2R (R = indenyl, norpinanyl, chloropropyl, 3-(N-morpholin)propyl; Vin = vinyl), disilylalkylamine (SiHMe2)iPrNSiMe2(CH2)3Cl, and monosilyldialkylamines Me2NSiMe2R (R = indenyl, chloropropyl, 3-(N-morpholin)propyl) were investigated. 1H, 13C, and 29Si MAS NMR spectroscopy, nitrogen adsorption/desorption, infrared spectroscopy, and model reactions with calix[4]arene as a mimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 84 publications
3
53
0
Order By: Relevance
“…[18] After partial dehydroxylation at 270 8C/10 À3 torr, the maximum silanol surface sites accessible for this parent material M1 (pore diameter d p,ads = 3.4 nm, BET surface a s = 1023 m 2 g À1 , pore volume V p = 0.99 cm 3 g À1 ; Table 1 and Figure 1) was determined to be 3.16 mmol per gram of SiOH by 1,1,3,3-tetramethyldisilazane silylation. [19] With the aim of generating alkylated alkaline earth metal surface species, two grafting strategies were pursued.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] After partial dehydroxylation at 270 8C/10 À3 torr, the maximum silanol surface sites accessible for this parent material M1 (pore diameter d p,ads = 3.4 nm, BET surface a s = 1023 m 2 g À1 , pore volume V p = 0.99 cm 3 g À1 ; Table 1 and Figure 1) was determined to be 3.16 mmol per gram of SiOH by 1,1,3,3-tetramethyldisilazane silylation. [19] With the aim of generating alkylated alkaline earth metal surface species, two grafting strategies were pursued.…”
Section: Resultsmentioning
confidence: 99%
“…All solvents were stored in a glovebox. Compound MCM-41 (M1), [18] 1, [16] 2 [16] 3, [17c] and MgMe 2 [43] were synthesized according to literature procedures. TEA was purchased from ABCR and used as received.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The postsynthesis or grafting method consists in grafting the functional groups after the surfactant removal, either by extraction or calcination, has been carried out [74]. This method offers a wide range of chances to allocate diverse functional groups in MSNPs and also allows to chemically attach delicate organic functions prone to hydrolysis and elimination reactions [75]. One of the major issues of postsynthesis method is the possible blocking of the mesopore openings by the functional groups, which would lead unavoidably to heterogeneous functionalization of the mesoporous matrix [76].…”
Section: Their Applications As Drug Delivery Systemsmentioning
confidence: 99%
“…In this case experiments were performed by using repetition times from 10 to 300 s based on literature data for similar samples. 28 The results obtained with commercial silica NPs indicated that the repetition time of 60 s could be used to obtain quantitative Si spectra with enough signal-to-noise ratio to integrate the spectra. The external references used for the chemical shifts were the CH 3 signal of hexamethylbenzene at 17.3 ppm for 13 C and the Q 3 Si sites of caulinite at -91.5 ppm for 29 Si.…”
Section: Methodsmentioning
confidence: 99%